A road map for enhancing the entrepreneurial knowledge potential of the lebanese small and medium-sized enterprises - Ibrahim Matar; Jurgita Raudeliūnienė (Open Economics, 2018)
Small and medium-sized enterprises (SMEs) in Lebanon constitute 90% of the country's enterprises (Kheir 2017). The Lebanese SMEs' entrepreneurial knowledge potential is not systematically developed to leverage the country's SMEs with a competitive advantage. Thus, the purpose of this article is to analyse knowledge management processes and to show how their implementation can work as a road map for enhancing the entrepreneurial knowledge potential of the Lebanese SMEs. Using the comparative analysis method along with the scientific literature review, the article will highlight knowledge management implementation gaps that have to be considered by entrepreneurs while establishing their SMEs focusing on the positive outcomes after implementation.
Keywords: M1; M16; D08; D83; 330; Evaluation; Knowledge Management; Knowledge Management Cycle; Knowledge Management Process; Knowledge Potential; Lebanese Small And Medium-Sized Enterprises